A Method for Designing Complex Machine Olfaction System - Hua Fang; Minglei Shu; Yunxiang Liu; Wanjun Yu; Wenju Li (Institute of Advanced Engineering and Science, 2014)
In the paper a template technology has been applied to the complex platform of machine olfaction system. The simulation sensor array template receives field odor data or simulates the data via recorders in database, then transmits to the platform which consists of several distributed monitoring subsystems. Each subsystem matches a set of gas sensors array, and has functions of logging data, communicating and simulating industry application. The data from the subsystem and the preprocessed data are sent to the web server center and stored in the databases. Then sensors perform analysis by several layer algorithms. And the exchanging algorithms convert the field odor data to gas concentrations with ppm values, the expert systems or recognition algorithms analyze the ppm values and show the application results. All data of each layer are stored in server database systems, and each layer algorithms can be updated and saved. Finally, the supporting platform that applied to industrial monitoring systems, was developed with a kind of industrial configuration softwares, web MIS and databases, and was utilized to realize monitor to the environmental systems by the simulation template. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5451